EVALUASI IMPLEMENTASI DAN PENYEMPURNAAN PERATURAN DAERAH NOMOR 16 TAHUN 2015 TENTANG PERLINDUNGAN DAN PEMENUHAN HAK PENYANDANG DISABILITAS DI KABUPATEN MANGGARAI - Ursula Idam Putri, Frederika Bernadeta; Alfira Nata, Maria; Lobo, Ferdinandus (Gapenas Publisher, 2024)
This study aims to evaluate the implementation of Regional Regulation (Perda) Number 16 of 2015 concerning the Protection and Fulfillment of the Rights of Persons with Disabilities in Manggarai Regency, as well as identify the obstacles faced in its implementation. This study uses an empirical juridical approach by collecting primary data through interviews and observations in the field, as well as secondary data from literature studies. The results of the study show that although this Regional Regulation has become an important legal foundation, its implementation still faces various challenges, including the lack of accessibility facilities in public places, lack of understanding of public service officers, limited access to information for people with disabilities, and lack of monitoring and evaluation of existing policies. To increase the effectiveness of the Regional Regulation, it is recommended to improve provisions that are more responsive to the times and the needs of people with disabilities, as well as to improve accessibility facilities, training for public service officers, and the fulfillment of inclusive access to information. This research is expected to contribute to the formulation of better policies to ensure the protection and fulfillment of the rights of persons with disabilities in Manggarai Regency.